Jesse's daycare - Valens, Amy.; Brown, Richard E. (Richard Eric), 1946 (Boston : Houghton Mifflin, 1990)
Compares the daily events of mother and son as one goes to work and the other goes to day care.
Keywords: Day care centers -- Fiction; Parent and child -- Fiction